Adolescents' Academic Emotions and Academic Achievement Across the Transition to Lower Secondary School: The Role of Learning Difficulties. Issue 3 (16th April 2021) - Sainio, Petra; Eklund, Kenneth; Hirvonen, Riikka; Ahonen, Timo; Kiuru, Noona
ABSTRACT: This study examined the role of learning difficulties in academic emotions and achievement across the transition to lower secondary school among 848 Finnish adolescents. Reading difficulties (RD) and math difficulties (MD) were identified based on test scores in Grade 6 and 7. Students with difficulties were identified as having resolving, emerging, or persistent RD/MD. Students rated their academic emotions and information on students' academic achievement was acquired from school registers. The results showed that a decline in academic emotions and achievement was typical among all students across the transition. Resolving, emerging, or persistent types of RD/MD were also meaningfully reflected in the development of academic emotions across the transition. Generally, the results showed that RD/MD students had a higher proclivity to experience more negative academic emotions than their peers, and they lagged behind their peers in achievement across the transition.